The Relationship between Urban Form and Station Boardings for Bogota's BRT - Estupinan, Nicolas; Rodriguez, Daniel A. (2012)
Despite emerging evidence about the association between the built environment and travel behavior, the relationship between bus transit demand and urban form remains largely unexplored. By relying on primary and secondary data analyzed with a geographic information system, this paper examines the built environment characteristics related to stop-level ridership for Bogota's successful bus rapid transit system. After accounting experimentally and statistically for the simultaneity between transit supply, transit demand, and the built environment, we find evidence of the importance of the built environment in BRT station boardings. Specifically, environmental supports for walking and personal and environmental barriers to car use were related to higher BRT boardings. Our results underscore the importance of urban environmental interventions to support transit use.